On the Effect of Echoes in Hybrid Terrestrial-Satellite Single Frequency Networks: Analysis and Countermeasures - Alberto Rico-Alvariño; C. Mosquera (2012 6th Advanced Satellite Multimedia Systems Conference (ASMS) and 12th Signal Processing for Space Communications Workshop (SPSC) (ASMS/SPSC 2012), 2012)
Hybrid Terrestrial Satellite Single Frequency Networks achieve large spectral efficiencies due to a higher frequency reuse, which is attained by transmitting the same waveform in the same frequency band from satellite and terrestrial transmitters. However, the presence of multiple transmitters propitiates the existence of the so-called SFN echoes, which can degrade the system performance even if they arrive within the OFDM guard interval. In this paper we characterize this effect by resorting to PER prediction metrics (or effective SNR metrics), and analyze two simple preprocessing schemes that mitigate this degradation: the use of Alamouti space-time codes, and a convenient prefiltering at the terrestrial transmitter.
Keywords: dynacs; Effective SNR; Hybrid Terrestrial- Satellite; satcom; Satellite OFDM; Single Frequency Network; Space-Time Coding